The Philosophy of Piers Plowman - Strong, David. author. aut Link
VII, 224 p.
Keywords: This book examines William Langland’s late medieval poem, The Vision of Piers Plowman, in light of contemporary intellectual thought. David Strong argues that where the philosophers John Duns Scotus and William of Ockham revolutionize the view of human potential through their theories of epistemology, ethics, and freedom of the will, Langland vivifies these ideas by contextualizing them in an individual’s search for truth and love. Specifically, the text ponders the intersection between reason and the will in expressing love. While scholars have consistently noted the text’s indebtedness to these higher strains of thought, this is the first book-length study in over thirty years that explores the depth of this interconnection, and the only one that considers the salience of both Scotus and Ockham. It is essential reading for medieval literary specialists and students as well as any cultural historian who desires to augment their knowledge of truth and love.